Der Stadtstaat Bremen - Abel, Herbert (ERDKUNDE, 1955)
The city state of Bremen is the smallest amongst the Länder of the Federal German Republic. Its political independence, which had already developed during the Middle Ages, arises, in the same way as that of Hamburg, from its function as a commercial centre and port of world importance. Its independence within the Holy Roman Empire was accorded recognition rather late, in 1646. Since the Congress of Vienna (1815) Bremen has held the same political status as the other German states. This status is not an end in itself but a means of fulfilling the tasks which fall to Bremen on account of its geographical position; tasks rooted in ocean shipping and world-wide trade. Because of the advancing silting up of the Lower Weser it was necessary to construct the outport Bremerhaven at the mouth of the Weser on a strip of land ceded by the Kingdom of Hanover (1827). During further development the area of Bremerhaven was increased several times by acquisition of land from Hanover and Prussia. Thus, by acquiring additional harbour space, it was possible to keep pace with the increasing trans-ocean trade which rose steeply in particular after the foundation of the Norddeutscher Lloyd shipping company in 1857. The originally Hanoverian and subsequently Prussian towns of Geestemünde and Lehe, which grew up in the neighbourhood of Bremerhaven, were joined together in 1924 under the name Wesermünde. Since 1947 the entire conurbation at the mouth of the Weser has become a part of' the Land Bremen, which therefore consists of the city of Bremen itself and the towns of the Lower Weser, now joined together under the name Bremerhaven. Bremerhaven is today the largest continental fishing port of Europe. Within the city sphere of Bremen, from the second half of the 19th century onward, port industries developed, based on the processing of imported raw materials, and thus depending on the navigation channel of the Lower Weser as far as it is suitable for ocean-going vessels. For the sites of the industrial plants which were founded by the Bremen merchants and ship-owners, places on Prussian and Oldenburg soil were first chosen since Bremen, with its bias towards free trade even after the foundation of the German Empire, did not belong to the German Customs Union and the customs duty as a rule was much higher on finished goods than on raw materials. Only after it joined the Customs Union in 1888, while at the same time constructing the free port of the city itself and carrying out the straightening of the Lower Weser, industrial plants were also located in the state of Bremen itself. In this respect, after the turn of the century, the chairman of directors of the Norddeutscher Lloyd, Johannes Wiegand, showed particular initiative. He pointed out that the trade and shipping of Bremen would in the future be increasingly subjected to crises and that in the interest of a stabilisation of the economic structure of the city state, the foundation of industrial enterprises was essential. In its oversea trade the emphasis lies again on imports. The most important commodities are cotton, wool, tobacco, timber, grain, coffee, wine and rice. As regards Bremen's connection with its hinterland, the main share of its inland traffic goes to the centres of economic activity within the Federal Republic, especially the Land North Rhine-Westphalia. Its connexions with its immediate neighbour, the Land Lower Saxony, which surounds it, are by no means negligible, but there can be no doubt that the Bremen ports serve first of all the entire Federal Republic and in parts an even wider area. Bremen, like Hamburg, believes that it can fulfil these sea-port functions efficiently only if it can retain in the future its independent status, be it within Germany as a whole or the Federal Republic.